Interfacing the Modifiable Multitasking Environment with ACT-R for Computational Cognitive Modeling of Complex Tasks. (September 2018) - Blaha, Leslie M.; Carlsen, Leif; Halverson, Tim; Reynolds, Brad
We demonstrate a set of software tools designed to facilitate computational cognitive modeling of multitasking performance. The Modifiable Multitasking Environment (ModME) offers a flexible, browser-based platform for creating multitasking experiments. Simplified Interfacing for Modeling Cognition–JavaScript (SIMCog-JS) provides communication between the browser-based experiments in ModME and the Java implementation of the ACT-R cognitive architecture. The baseline configuration of these software packages enables an ACT-R model to perform pilot-like multitasking in the modified Multi-Attribute Task Battery, which is implemented as the baseline task available in ModME. We show how this combination facilitates the development of models for assessing multitasking workload. In this demonstration, we will explain the software packages and allow attendees to interact with system elements, particularly the ModME graphical user interfaces. All software is available open source for attendees to try themselves.